A proposed model for managing investment in sports tourism and its impact on sustainable development in Saudi Arabia - Selim, Hossam S; Alnasser, Yousif; Alkhudhayr, Ibrahim H; Alessa, Fatimah; Hassan, Ahmed K (International Journal of Management and Sustainability, 2025)
To develop a framework for managing investments in the sports tourism industry and to explore how these investments contribute to achieving sustainable development goals in Saudi Arabia. It employs both inductive and descriptive approaches, incorporating theoretical analysis, critical reviews, and quantitative surveys. The findings indicate that investing in sports activities offers numerous significant benefits and positively impacts the economic appeal and future potential of the industry. This, in turn, can facilitate progress in the three pillars of sustainability: economic, social, and environmental dimensions. The study concludes with recommendations, the most important of which is the need for collaboration and integration across all sectors concerning financial aspects and incentives to attract investors. Additionally, it emphasizes the importance of staying attuned to emerging opportunities to maximize advantages in the industry. Furthermore, there is an urgent need to align with legislative advancements by adapting investment regulations in the sports sector to fit the Saudi context and by addressing any barriers that could obstruct these investments. These actions will help achieve the expected returns from the sports tourism industry.